Right to transfer: prohibition and restraints / Mat Ghani Abdullah - Abdullah, Mat Ghani (Faculty of Law, 1985)
Torrens System is a system of land dealing and founded in Australia in beginning of 19th century. The Torrens System evolved in its place of origin as a statutory system of conveyancing. Its fundalmental principle is registered ownership of land which may safely be relied upon by a bonafide purchaser in buying the land or taking any interest therein from the registered owner. In so far as the Torrens System operates for the purposes of setting, by virtue of registration, the ownership for the title to a piece of private land in order to facilitate transfer or other dealings therein, it only concerns legal relationships between private person in respect of the land...